A new benzophenone from garcinia benthamiana - See, Irene; Cheng, Gwendoline Lian Ee; Soek, Sin Teh; Siau, Hui Mah; Karjiban, Roghayeh Abedi; Daud, Shaari; Yi, Vivien Mian Jong (ACG Publications, 2016)
A detailed phytochemical study on the stem bark of Garcinia benthamiana has afforded a new benzophenone, benthamianone (1), together with congestiflorone (2), a mixture of stigmasterol (3) and γ-sitosterol (4) as well as a mixture of phloroglucinol (5) and methyl palmitate (6). The structural elucidation of these compounds was performed through analysis of their spectroscopic data (NMR spectra and MS). This is the first report on the phytochemistry of Garcinia benthamiana.